Relationship between health, lifestyle, psychosocial factors and academic performance: a cross-sectional study at the University of Salerno - Silvana Mirella Aliberti; Pierpaolo Cavallo; Mario Capunzo; Sergio Brongo; Luca Giraldi; Emanuela Santoro; Giovanni Boccia (Epidemiology, Biostatistics and Public Health)
Background: The relationship between health indicators and quality of life is significantly important in clinical decisions. Health policy and an individual’s quality of life are important factors contributing to an individual's decisions and preferences. University students constitute a large part of the country's young population, so a healthy lifestyle is of crucial importance for this group. The aim of the present study was to investigate healthy lifestyle habits and its relationship with academic performance in undergraduate students of the University of Salerno. Methods: A cross-sectional study was conducted among undergraduate students of the University of Salerno. Data were collected by a self-report anonymous questionnaire. The field research was conducted among students of the University of Salerno in the academic years 2014/2015, from October to March. Descriptive statistics were used to describe sample characteristics. Test of proportions was used to test the differences between blocked and regular students. Analysis were conducted using STATA software. Results: A total of 519 students formed the sample. In total, 248 (47.78%) claimed to have blocks in their studies and among them 214 (86.29%) were out of course. The status of blocked students’ health promotion behaviors was significantly favorable compared to that of regular students. General health perception of the regular students yielded worse results than of the blocked students. Anxiety and depression were greater in regular students than blocked students. Conclusion: Results from the present study support our hypothesis of a relationship between health, lifestyle, psychosocial factors and academic performance: students with blocked had better health and lifestyle than regular students. Their attitude to resilience emerged from the ability to overcome difficult situations, but also from an attitude of arrogance despite being aware of the ability to study successfully. Probably the blocked in the studies was due to low self-esteem. Key words: university life, lifestyle, health, psychosocial factors, academic performance